1975
DOI: 10.1002/zaac.19754130304
|View full text |Cite
|
Sign up to set email alerts
|

Beiträge zur Chemie des Phosphors. 59. Zur Synthese und Struktur von (C6H5PS)3

Abstract: 1,2,4‐Triphenyl‐1‐thio‐cyclo‐3,5‐dithia‐1,2,4‐triphosphan (C6H5PS)3 (1) wird durch Reaktion von Dikalium‐triphenyl‐triphosphid (4) mit Dichlortrisulfan sowie durch Umsetzung von Phenylphosphin mit Schwefeldichlorid in sehr guter Ausbeute erhalten. Außerdem bildet sich 1 – zusammen mit dem Cyclo‐thia‐phosphan (C6H5P)4 (3) – bei der Umsetzung von 1,2‐Diphenyl‐1,2‐dihalogen‐diphosphanen mit Schwefelwasserstoff oder Disulfan sowie aus 4 und Dischwefeldichlorid. – Die Gesamtheit der spektroskopischen Befunde, insbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…The solid-state structures of 2Ch resemble those previously reported. 23,25,26 data is similar to that found for 2S. The same is true also for P-Ch bond distances in 7SCu, 7SAg, and 2S: 2.1334(16), 2.128(2) and 2.1393(2) Å, respectively.…”
Section: X-ray Crystallographysupporting
confidence: 83%
See 1 more Smart Citation
“…The solid-state structures of 2Ch resemble those previously reported. 23,25,26 data is similar to that found for 2S. The same is true also for P-Ch bond distances in 7SCu, 7SAg, and 2S: 2.1334(16), 2.128(2) and 2.1393(2) Å, respectively.…”
Section: X-ray Crystallographysupporting
confidence: 83%
“…19,20 While there have been extensive studies on P(V)-Ch derivatives, examples of P(III) within the ring core are more uncommon, especially in regards to those with a general formula (RPCh)n. Examples of (RPCh)n have been reported for n = 2, 3, and 4, where bulky R groups are required to kinetically stabilize the P(III) centre ( Figure 1, B-D). [21][22][23][24][25][26] In particular, our group has recently reported the syntheses of strained (RPCh)2 rings 1Ch (Ch = S, Se) with P in the +3 oxidation state, the first representatives of these strained compounds, by installing m-terphenyl substituents at phosphorus. 24 Although select examples of (RPCh)n have been reported since the early 1980's, a thorough examination of their chemistry has not been published, though related P(III)-Ch-N macrocycles have been reported to form polynuclear Ag(I) sandwich complexes upon reaction with various amounts of AgOTf (Figure 1, E).…”
Section: Introductionmentioning
confidence: 99%
“…The "P NMR is second order, even at 101.4 MHz. The pattern is similar to that given by the tetraphospholanes [20-231. When (PhP)5 and sulphur are reacted together such that the P:S ratio is 1 : 1, (PhPS), is produced [22]. When a 1 : 1 PhP: Se ratio is refluxed in toluene for 2 h, the 31P NMR spectrum reveals the presence of 3 together with 5.…”
Section: Resultsmentioning
confidence: 99%
“…was used as received. (PhP)5 [15] and (PhPS)3 [4] were prepared by literature methods. Li2Se was prepared by an adaptation of a published method [16].…”
Section: Methodsmentioning
confidence: 99%
“…In the recent past, phosphinidene chalcogenides (R-PvE) have been employed in transition metal chemistry, [82][83][84] cycloaddition reactions, designing many unique phosphine ligands, 85,86 and also in the construction of larger [RPE] n rings (D and E, Chart 1). [87][88][89] Although numerous examples of the type [RPE] 2 (C, Chart 1) with pentavalent phosphorus atoms are known, 64,90,91 the series of the type [RPE] 2 with trivalent phosphorus atoms is unstable and less extensive. Mechanistic investigations using density functional theory (DFT) calculations suggested that the P III centers in C (Chart 1) can exhibit a Lewis acidic character and often readily react with strong nucleophiles like NHCs and cleave the four-membered ring by trapping the monomers Ar*-PvS and Ar*-PvSe.…”
Section: Dalton Transactionsmentioning
confidence: 99%